2005
DOI: 10.1021/ja053998c
|View full text |Cite
|
Sign up to set email alerts
|

Green Chemical Functionalization of Single-Walled Carbon Nanotubes in Ionic Liquids

Abstract: Single walled carbon nanotubes (SWNTs) are exfoliated and functionalized predominantly as individuals by grinding them for minutes at room temperature with aryldiazonium salts in the presence of ionic liquids (ILs) and K(2)CO(3). This constitutes an extremely rapid and mild green chemical functionalization process for obtaining the individualized nanotube structures. A number of ILs and various reaction conditions were surveyed. Raman, XPS, UV/vis/NIR spectroscopies, thermogravimetric analysis, and atomic forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(131 citation statements)
references
References 18 publications
4
124
0
3
Order By: Relevance
“…The suspension concentrations of SWCNTs promoted by HvimiBr are increased by at least 20% with respect to commonly used surfactants, such as sodium dodecyl sulfate, sodium dodecyl benzene sulfonate and cetyl trimethyl ammonium bromide. Moreover, it has been found that SWCNTs bundles are simultaneously exfoliated and chemically functionalized predominantly as individuals by grinding them with aryl diazonium salts in Imi-ILs [60]. This reaction occurs in minutes at room temperature, and is an extremely rapid and mild green protocol to exfoliate and functionalize SWCNTs.…”
Section: Carbon Nanotubes In Imidazolium Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The suspension concentrations of SWCNTs promoted by HvimiBr are increased by at least 20% with respect to commonly used surfactants, such as sodium dodecyl sulfate, sodium dodecyl benzene sulfonate and cetyl trimethyl ammonium bromide. Moreover, it has been found that SWCNTs bundles are simultaneously exfoliated and chemically functionalized predominantly as individuals by grinding them with aryl diazonium salts in Imi-ILs [60]. This reaction occurs in minutes at room temperature, and is an extremely rapid and mild green protocol to exfoliate and functionalize SWCNTs.…”
Section: Carbon Nanotubes In Imidazolium Ionic Liquidsmentioning
confidence: 99%
“…Especially in 2003, Fukushima et al [59] first found that the heavily entangled SWCNT bundles were well untangled in Imi-ILs after being ground. Afterwards, Tour et al [60] have demonstrated that SWCNTs are effectively exfoliated and functionalized predominantly as individuals by grinding with aryl diazonium salts in the presence of ILs as green solvents. Recently, Han et al [61] have reported that graphene sheets are stably dispersed in an Imi-IL of 1-butyl-3-methylimidazolium hexafluorophosphate (BmimPF 6 ) with the help of poly(1-vinyl-3-butylimidazolium chloride) [poly(VbimCl)].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 schematically illustrates the preparation of AMSN free-standing film. In brief, MWNTs (average diameter: 10 nm) were mixed with a pyridinium-based ionic liquid (1-butyl-4-methylpyridinium tetrafluoroborate), which has an ionic conductivity of 1.854 mS cm -1 [20] and is known to effectively disperse nanotubes [21] without causing substantial damage to the nanotubes [22].…”
Section: Characterizationmentioning
confidence: 99%
“…Vivekchand et al, (2007) have extensively reviewed functionalization of nanotubes and nanowires by various methodologies. For example, SWNT can be functionalized in ionic liquid using a mortar and pestle (Scheme 4) (Price et al, 2005). SWNTs can be cut into short segments by controlled oxidation by piranha (HNO 3 /H 2 SO 4 ) solutions [Ziegler, 2005].…”
Section: Functionalization Of Nanoreinforcementsmentioning
confidence: 99%